Learning Pronunciation Through Voice Recording Students At Universitas Graha Nusantara - Siregar, Rini Kesuma (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
Learning about English pronunciation is one of the obstacles for every student who is or wants to learn. This happens because the mother tongue of the Indonesian people, most of the languages from their respective regions. This research uses descriptive research method, because it focuses on how students pronounce in English. The population of three students at Universitas Graha Nusantara is 28 students. The result shows that there are six effect of pronunciation learning, theya are native language, the age factor, amount of expusere, phonetic ability, attitude and identity, and motivation and concern for good pronunciation. Beside that, combinations of sounds, word stress, rythm and intonation also the problem of the students in learning pronunciation, and through practice with voice recording students' abilities in pronunciation improve and become better.